(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Hairy polyp or dermoid is a benign bigerminal congenital germ cell tumour. It is a rare condition in the nasopharynx. Hairy polyp in head and neck region consists less than 5% of that occurs in whole body. Objective: To report a rare nasopharyngeal benign condition presented without obstructive symptoms. Case: A four-year-old female child presented with a pedunculated dermoid tumour attached to the left lateral wall of nasopharynx. There was an associated unilateral cleft in soft palate. The tumour was removed by dissecting with bipolar diathermy by combined endonasal endoscopic and transoral approach. Conclusion: Hairy polyp in nasopharynx may present as an incidental asymptomatic mass in throat and may be associated with a cleft palate. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 92-95